2014
DOI: 10.1007/s00299-014-1632-5
|View full text |Cite
|
Sign up to set email alerts
|

Methyl jasmonate represses growth and affects cell cycle progression in cultured Taxus cells

Abstract: Methyl jasmonate (MeJA) elicitation is an effective strategy to induce and enhance synthesis of the anticancer agent paclitaxel (Taxol®) in Taxus cell suspension cultures; however, concurrent decreases in growth are often observed, which is problematic for large scale bioprocessing. Here, increased accumulation of paclitaxel in Taxus cuspidata suspension cultures with MeJA elicitation was accompanied by a concomitant decrease in cell growth, evident within the first three days post-elicitation. Both MeJA-elici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
34
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(39 citation statements)
references
References 64 publications
5
34
0
Order By: Relevance
“…These observations correspond to the results of previous investigations (Sykłowska- Baranek et al 2015b), where root growth in PFD supported cultures after elicitation with MJ was higher than in that elicited without perfluorinated phases, degassed or aerated. The results of current study are also consistent with data published by Patil et al (2014) which indicates that cell growth in suspension cultures of T. cuspidata upon elicitation with MJ could be attributed to slowed down cell cycle progression, an increase in G0/G1 phase cells and a reduced number of actively dividing cells rather than necrosis.…”
Section: The Influence Of Culture Conditions On Hairy Root Biomass Insupporting
confidence: 93%
“…These observations correspond to the results of previous investigations (Sykłowska- Baranek et al 2015b), where root growth in PFD supported cultures after elicitation with MJ was higher than in that elicited without perfluorinated phases, degassed or aerated. The results of current study are also consistent with data published by Patil et al (2014) which indicates that cell growth in suspension cultures of T. cuspidata upon elicitation with MJ could be attributed to slowed down cell cycle progression, an increase in G0/G1 phase cells and a reduced number of actively dividing cells rather than necrosis.…”
Section: The Influence Of Culture Conditions On Hairy Root Biomass Insupporting
confidence: 93%
“…Large number of studies on the high throughput sequencing of plant transcriptome in many model and non model species, such us maize, grapevine, Taxus , eucalyptus, olive and cucumber etc. have been undertaken1920212223. Comparative global transcriptome analysis is a powerful approach for discovering the molecular basis underlying specific biological events242526.…”
mentioning
confidence: 99%
“…It has been reported that the time of elicitation is one of the key factors that affect cell growth and production of secondary metabolites in plant cell suspension cultures. Thus, in Taxus cell cultures, the repression of the growth through inhibition of cell cycle progression by MeJA elicitation occurs accompanied by the increased accumulation of paclitaxel (Patil et al 2014). In Panax notoginseng cell cultures, elicitation with jasmonate derivates during the early exponential phase of growth up-regulate squalene synthase and squalene epoxidase, two common enzymes of triterpene and sterol biosynthesis, but down-regulate the sterol related cycloartenol synthase transcription, which implies that oxidosqualene can be directed from sterol to ginsenoside biosynthesis (Hu and Zhong 2008).…”
Section: Effect Of Ja Concentration and Time Of Elicitationmentioning
confidence: 97%